2008
DOI: 10.1636/ct07-116.1
|View full text |Cite
|
Sign up to set email alerts
|

Spiders in wheat fields and semi-desert in the Negev (Israel)

Abstract: Intensively cultivated arable land and semi-desert are two dominant habitat types in the arid agroecosystem in the northwest Negev Desert (Israel). The present study compares activity-densities and species richness of spiders in these distinctive habitat types. Sixteen wheat fields and twelve locations in the semi-desert were sampled during the winter growing season of wheat. Semi-desert habitats had more spider species and higher spider activity-densities than irrigated wheat fields. The majority of spider fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 24 publications
(35 reference statements)
2
31
1
2
Order By: Relevance
“…1), the model estimates suggest that a higher proportion of the spider population in wheat are recruited for crop immigration than in remnant vegetation. This result is in line with observations that crops are often dominated by spider species that have the ability to disperse by ballooning (Pearce et al 2005;Gavish-Regev et al 2008, Pluess et al 2008 and that the ballooning propensity is higher in spiders originating from disturbed habitats, such as crops, than from undisturbed habitats, such as remnant vegetation (Entling et al 2011). Furthermore, increased spider ballooning from wheat crops could have been triggered by wheat harvest, which coincided with the time that the experiment was conducted.…”
Section: Discussionsupporting
confidence: 88%
“…1), the model estimates suggest that a higher proportion of the spider population in wheat are recruited for crop immigration than in remnant vegetation. This result is in line with observations that crops are often dominated by spider species that have the ability to disperse by ballooning (Pearce et al 2005;Gavish-Regev et al 2008, Pluess et al 2008 and that the ballooning propensity is higher in spiders originating from disturbed habitats, such as crops, than from undisturbed habitats, such as remnant vegetation (Entling et al 2011). Furthermore, increased spider ballooning from wheat crops could have been triggered by wheat harvest, which coincided with the time that the experiment was conducted.…”
Section: Discussionsupporting
confidence: 88%
“…One study measures spider activity density in wheat fields and adjacent natural semi-desert in Israel. The authors argue that their data showed a strong preference among sheetweb spiders for agricultural habitat that supports the conclusion that in these semi-desert habitats, sheetweb spiders are moving from wheat fields to adjacent semi-natural desert lands (Pluess et al, 2008). Another study found that wheat-dominated landscapes appear to augment generalist predators (ladybird beetles and spiders) of nettle aphids resulting in dramatically higher natural enemy-prey ratios and reduced aphid density in adjacent nettle patches (Rand and Tscharntke, 2007).…”
Section: Spillover From Managed To Natural Systemsmentioning
confidence: 66%
“…generalist Holzschuh et al (2011) pollinator Germany Bombus spp. generalist Pluess et al (2008) predator Israel Spiders (94 spp.) generalist Rand and Tscharntke (2007) predator Germany Spiders and Coccinelld beetles generalist Rand and Louda (2004) predator USA (Nebraska) Rhinocyllus conicus specialist Estrada and Coates-Estrada (2002) seed disperser Mexico Bats (50 spp) generalist Galindo-Gonzalez et al (2000) seed disperser Mexico Bats (20 spp) generalist Laborde et al (2008) seed disperser Mexico Vertebrate frugivores generalist Herrera and Garcia (2009) seed disperser Spain Birds generalist Tewksbury et al (2002) seed disperser USA (South Carolina) Birds generalist…”
Section: Discussionmentioning
confidence: 99%
“…Thus we predicted that a high percentage of non-crop habitats in the surrounding landscape should increase both species richness and activity-densities of spiders in wheat fields. In contrast to the majority of the other spider families, the crop-dominating Linyphiidae show a strong preference for cropland in the northwest Negev Pluess et al, 2008), and we therefore expected a lower activity-density of Linyphiidae in landscapes with high percentages of non-crop habitats. Further, arthropods respond to the surrounding landscape at different spatial scales depending on their dispersal abilities (Steffan-Dewenter et al, 2002;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…The present study aims at supplying this knowledge. Given the high mobility of spiders, we expect that the composition of the surrounding landscape would affect local spider communities in wheat fields as follows: Species richness and activity-density of spiders in wheat fields in the northwest Negev are lower than in noncrop habitats during the winter cropping season (Pluess et al, 2008). Thus we predicted that a high percentage of non-crop habitats in the surrounding landscape should increase both species richness and activity-densities of spiders in wheat fields.…”
Section: Introductionmentioning
confidence: 99%